Endoscopic discectomy for L4–L5 disc herniation: percutaneous endoscopic transforaminal discectomy vs. unilateral biportal endoscopic discectomy - Chen, Huan; Chen, Long; Zhang, Yu (Frontiers in Surgery, 2025)
Study designRetrospective evaluation.ObjectiveThis study aims to compare the clinical outcomes of percutaneous endoscopic transforaminal discectomy (PETD) and unilateral biportal endoscopic discectomy (UBED) in the management of L4–L5 disc herniation, and to identify the procedure most suitable for different types of herniations.MethodsData were retrospectively collected from patients with L4–L5 disc herniation who underwent PETD or UBED between March 2018 and December 2019. Each group consisted of 34 consecutive patients. Key outcomes, including blood loss, operation time, fluoroscopic time, hospitalization duration, and herniation type, were analyzed and compared. Clinical efficacy was assessed using the Oswestry Disability Index (ODI), Visual Analog Scale (VAS), and modified MacNab criteria.ResultsSignificant differences were observed between the groups in terms of blood loss, operation time, and fluoroscopic time. Both groups demonstrated significant improvements in VAS scores for back and leg pain, as well as ODI. The proportion of patients achieving excellent or good outcomes was 88.2% for PETD and 91.2% for UBED. Notably, the PETD group had a higher proportion of intervertebral foramen-type disc herniations (32.4%) compared to the UBED group (2.9%; P < 0.05). Migration-type herniations were more frequently removed with UBED (35.3%) than with PETD (5.9%; P < 0.05).ConclusionPETD is associated with less blood loss and shorter operation time, making it the preferred choice for intervertebral foramen-type herniations. UBED, with its shorter fluoroscopic time and reduced puncture difficulty, is more suitable for migration-type herniations. Both techniques are effective for treating central, axillary, and shoulder-type disc herniations. With proper patient selection, both PETD and UBED are safe and effective for L4–L5 disc herniation.